Pengaruh Kajian Kitab Safinatun Najah Terhadap Peningkatan Ibadah Shalat Peserta Didik - edy; Maulana Pikri Padillah (Edusifa: Jurnal Pendidikan Islam, 2024)
The background problem of this research is the study of the book Safinatun Najah which can influence students' prayer worship. The problem in this study is formulated as follows: how is the influence of the study of the book Safinatun Najah on increasing students' prayer services. The purpose of this study was to determine the effect of the study of the Safinatun Najah on improving students' prayer services.             The method used in this research is descriptive quantitative method, while the data collection technique used is literature study and field research in the form of observation, interviews and questionnaires. The population in this study were the ibtida' Assalafiyah Al-Karimah Islamic Boarding School as many as 27 people. The sample used in this research is saturated sampling technique, namely the sampling technique when all members of the population are used as samples. And the technique of data analysis from this study is quantitative analysis, namely analysis carried out by statistical analysis, namely descriptive statistics, and looking for percentages with formulas. From the results of the research conducted, there is a positive correlation between the study of the book Safinatun Najah and the improvement of students' prayer services in the ibtida' Assalafiyah Al-Karimah Islamic Boarding School. This is indicated by the rxy value of 0.537, where the correlation index is included in the category of quite strong and significant at a significant level of 5% namely 0.396 and 1% 0.505 thus the proposed hypothesis is accepted, namely there is a positive correlation between variable X and variable Y   Keywords: Study, Safinatun Najah, sholat